Effect of Water Regime and Nitrogen on Growth, Productivity and Economics of Summer Rice Varieties - Show, R.; Ghosh, D. C.; Malik, G. C.; Banerjee, M. (International Journal of Bio-resource and Stress Management, 2014)
The results of field experiment conducted during summer season of 2004 and 2005 showed that continuous field saturation increased plant height, tillers production, LAI, DMA, CGR, panicle and grain production, and test weight that ultimately produced high grain (6025 kg ha-1) and straw yield (6296 kg ha-1) with high harvest index, gross return and net return. IR-36 recorded higher number of tillers m-2, LAI, DMA, CGR, greater number of panicles m-2 and test weight and finally produced higher grain (5671 kg ha-1) and straw (6001 kg ha-1) yields and paid greater gross and net return than those of Annapurna. The crop receiving 120 kg N ha-1 (RDN) increased plant height, tiller production, LAI, DMA, CGR, recorded higher number of panicles m-2 and grains panicle-1 and produced higher grain and straw yield with higher return. The crop at continuous saturation with RDN recorded greater tiller production, LAI and CGR during reproductive period over most of the other treatment combinations. It increased panicle and grain production and produced the highest grain (6299 kg ha-1) yield and paid very high net return (` 16818 ha-1) from summer rice. IR 36 receiving RDN produced greater number of tillers m-2, LAI and CGR during reproductive period, recorded the higher number of panicles m-2 and grains panicle-1 and produced the highest grain yield (5882 kg ha-1) of summer rice over most of the other treatments. IR 36 at continuous saturation with RDN improved growth attributes, increased yield components, produced high grain yield and paid high net return under the study.